2010
DOI: 10.2298/ciceq091208020r
|View full text |Cite
|
Sign up to set email alerts
|

Titrimetric and spectrophotometric determination of doxycycline hyclate using bromate-bromide, methyl orange and indigo carmine

Abstract: One titrimetric and two indirect spectrophotometric methods are described for the determination of doxycycline hyclate (DCH) in bulk drug and in its formulations. The methods use bromate-bromide, methyl orange and indigo carmine as reagents. In titrimetry (method A), DCH is treated with a known excess of bromate--bromide mixture in acid medium and the residual bromine is back titrated iodometrically after the reaction between DCH and in situ bromine is ensured to be complete. In spectrophotometric methods, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Doxycycline is official in Indian Pharmacopoeia [2], British Pharmacopeia [3], United state Pharmacopeia [4], European Pharmacopeia [5], and Japanese Pharmacopeia [6]. From the literature review, it is observed that many analytical methods have been developed involving potentiometric [7], Differential pulse polarography [8], spectrophotometric [9–11], HPLC [12–15], and LC‐MS [16–17] for the estimation of DOX in pharmaceutical formulations. ORN Figure 2, chemically 1‐chloro‐3‐(2‐methyl‐5‐nitroimidazol‐lyl)Propan‐2‐ol [34].…”
Section: Introductionmentioning
confidence: 99%
“…Doxycycline is official in Indian Pharmacopoeia [2], British Pharmacopeia [3], United state Pharmacopeia [4], European Pharmacopeia [5], and Japanese Pharmacopeia [6]. From the literature review, it is observed that many analytical methods have been developed involving potentiometric [7], Differential pulse polarography [8], spectrophotometric [9–11], HPLC [12–15], and LC‐MS [16–17] for the estimation of DOX in pharmaceutical formulations. ORN Figure 2, chemically 1‐chloro‐3‐(2‐methyl‐5‐nitroimidazol‐lyl)Propan‐2‐ol [34].…”
Section: Introductionmentioning
confidence: 99%
“…Both ciprofloxacin and doxycycline hyclate are official in the British and United States Pharmacopoeia, and their official method of assay is high-performance liquid chromatography (HPLC) [1, 3]. Several analytical methods such as spectrophotometry [4, 5], fluorimetry [6], ultra-performance liquid chromatographic [7], HPLC [8], high-performance thin-layer chromatography [9], high-performance capillary electrophoresis [10], and capillary electrophoresis [11] have been reported for the determination of ciprofloxacin while spectrophotometry [12, 13] and HPLC [14, 15] are for the determination of doxycycline hyclate alone or in combination with other medicines.…”
Section: Introductionmentioning
confidence: 99%